MIGRANTS AND TUBERCULOSIS – AN EXTERNAL FACTOR OF ECOLOGICAL INFLUENCE - N. Yu. Isayeva (Sankt-Peterburg : NIIÈM imeni Pastera, 2015)
Tuberculosis is one of the most dangerous infections. First of all it strikes socially unprotected part of the population. The migrants which number grows in St. Petersburg, represent stress expressive category of the people reducing protective forces of immunity. Incidence of tuberculosis among migrants usually significantly exceeds incidence of permanent residents of the city. There are the difficulties connected with problems of adaptation, shortcomings of lows, finance. Thus, the influencing on ecological system of the city more than one million arrived migrants undoubtedly. It is necessary to prevent development of tuberculosis epidemic among migrants by providing with preventive inspection and complete treatment of all new cases of tuberculosis irrespective of their legal and social status.